Pelaksanaan Praktik Pengenalan Lapangan (PPL) di SMK dalam Meningkatkan Kompetensi Mengajar Mahasiswa Calon Guru Pemasaran - SHERLY MONICA (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Field Teaching Practice (Praktik Pengenalan Lapangan/PPL) is a program designed to provide authentic teaching experiences for preservice teacher students in carrying out their duties as prospective teachers in schools. This article aims to describe the implementation of PPL in Vocational High Schools (Sekolah Menengah Kejuruan/SMK), particularly in the subject of Accounting and Institutional Finance, and its role in enhancing the teaching competence of preservice teacher students.The writing method employed is descriptive qualitative, with data collection techniques including observation, interviews, and documentation conducted throughout the PPL activities. The results of the PPL indicate that students gained direct experience in developing instructional materials, implementing the teaching and learning process, managing classrooms, and conducting learning evaluations. In addition, the application of active and contextual learning methods was able to increase student participation and understanding.Therefore, PPL activities in vocational high schools play an important role in shaping professionalism and preparing students to become competent future educators.